Serum apelin levels: clinical association with vascular involvements in patients with systemic sclerosis. (24th November 2011) - Aozasa, N.; Asano, Y.; Akamata, K.; Noda, S.; Masui, Y.; Yamada, D.; Tamaki, Z.; Tada, Y.; Sugaya, M.; Kadono, T.; Sato, S
Abstract: Background Apelin is a bioactive peptide exerting its pro‐angiogenic and pro‐fibrotic effects in a context‐dependent manner through the activation of its receptor APJ, which is ubiquitously expressed on the surface of various cell types. The activation of apelin/APJ signalling appears to be involved in the pathological process of fibrotic disorders, including liver cirrhosis. Objective As an initial step to clarify the role of apelin/APJ signalling in the pathogenesis of systemic sclerosis (SSc), we investigated serum apelin levels and their clinical association in patients with SSc. Methods Serum apelin levels were determined by a specific enzyme‐linked immunosorbent assay in 56 SSc patients and 18 healthy controls. Results Serum apelin levels were comparable among three groups, including diffuse cutaneous SSc, limited cutaneous SSc and control subjects (1.77 ± 1.48, 1.63 ± 1.51 and 1.61 ± 0.44 ng/mL, respectively). When we classified SSc patients into three groups according to disease duration, serum apelin levels were elevated in early SSc (<3 years) compared with mid‐stage SSc (3–10 years) (1.74 ± 1.26 vs. 1.02 ± 0.52 ng/mL, P < 0.05). Importantly, in late stage SSc (>10 years), the prevalence of severe vascular involvements, including intractable skin ulcers, scleroderma renal crisis and pulmonary arterial hypertension, was significantly higher in patients with elevated serum apelin levels than in those without (100% vs. 20%, P < 0.05). Conclusion Apelin may be associated with altered and activated angiogenesis prior to fibrotic responses in early SSc and with the development of proliferative vasculopathy in late stage SSc.